Vertical structure of summer clear‐sky atmospheric boundary layer over the hinterland and southern margin of Taklamakan Desert. (July 2016) - Wang, Min Zhong; Lu, Hui; Ming, Hu; Zhang, Jiantao
ABSTRACT: The Urumqi Institute of Desert Meteorology of China Meteorological Administration carried out a scientific experiment to detect the clear‐sky atmospheric boundary layer by using a wind‐profiling radar and L‐band radar sounding system in the hinterland and southern margin of the Taklamakan Desert in the summer of 2010 and 2011. Based on wind profile and radiosonde data collected from this experiment, this paper analyses the vertical structure features of the clear‐sky daytime convective boundary layer and night‐time stable boundary layer in the hinterland and southern margin of the desert, and compared the result with the boundary layer features in the Tibetan Plateau and the Dunhuang region in Gansu. The results show that: (1) the summer clear‐sky convective boundary layers in the hinterland and southern margin of the Taklamakan Desert can develop thickly. The mixing layer can reach a maxiumum thickness of 3700 m, above which a significant entrainment layer exists with average thickness about 500 m. The maximum thickness of the convective boundary layer can exceed 4000 m. (2) A temperature inversion phenomenon is found to exist remarkably over the summer clear‐sky nights in the hinterland and southern margin of the desert. The thickness of the night stable boundary layer is about 400–600 m, but the residual layer above it generally can reach a thickness of more than 3000 m. (3) An atmospheric boundary layer with supernormal thickness under the clear summer sky is a phenomenon of arid regions in Northwest China.